Strategi Tenaga Kependidikan dalam Mengelola Administrasi di SPM Tsanawiyah Musthafawiyah Purba Baru (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the strategies implemented by education personnel in managing administration at SPM Tsanawiyah Musthafawiyah Purba Baru. Effective administrative management is one of the key factors in supporting the smooth educational process in madrasah. The research method used is descriptive qualitative with a case study approach. Data were collected through observation, in-depth interviews and documentation. The results showed that the education personnel at SPM Tsanawiyah Musthafawiyah Purba Baru has implemented various strategies in managing administration, including increasing competence through training, optimizing the use of information technology, developing a structured management system, and improving cooperation and communication between staff. Nevertheless, there are still some obstacles, such as limited human resources and infrastructure, which hamper the effectiveness of administrative management.